2013
DOI: 10.1074/jbc.m113.457499
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cell Adhesion Molecule (EpCAM) Regulates Claudin Dynamics and Tight Junctions

Abstract: Background: EpCAM is important for intestinal epithelial integrity and is also involved in tumorigenesis. Results: EpCAM interacts with claudin-7 and claudin-1, protects them from lysosomal degradation, and alters their intercellular distribution. Conclusion: EpCAM modifies tight junction composition and function by regulating amounts and locations of claudins. Significance: Effects of EpCAM on epithelial physiology and tumorigenicity may be mediated via modulation of claudins and tight junctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
135
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(145 citation statements)
references
References 50 publications
(54 reference statements)
9
135
1
Order By: Relevance
“…Mice with germline null mutations in Epcam develop the murine equivalent of CTE and die within 2 weeks after birth (10,11). Consistent with EpCAM's claudin-stabilizing effects (12), intestinal expression of selected claudins, including claudin-7, is markedly decreased in mice and humans with EPCAM mutations (3,10). The strong similarities between the phenotypes of Epcam and Cldn7 knockout mice suggest that EpCAM-claudin interactions are extremely important in the intestine (8,13,14).…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Mice with germline null mutations in Epcam develop the murine equivalent of CTE and die within 2 weeks after birth (10,11). Consistent with EpCAM's claudin-stabilizing effects (12), intestinal expression of selected claudins, including claudin-7, is markedly decreased in mice and humans with EPCAM mutations (3,10). The strong similarities between the phenotypes of Epcam and Cldn7 knockout mice suggest that EpCAM-claudin interactions are extremely important in the intestine (8,13,14).…”
Section: Introductionmentioning
confidence: 60%
“…Previous studies have identified the cell surface protease matriptase as an important regulator of tight junction composition and function, but detailed molecular mechanisms that link matriptase and tight junctions have not been delineated (21,22). EpCAM also modulates tight junctions, albeit in a reciprocal fashion (10,12). Whereas inhibition of expression of matriptase in Caco-2 cell monolayers increased permeability and decreased transepithelial electrical resistance (TEER) (21), inhibition of EpCAM expression by Caco-2 cells enhanced TEER in conjunction with decreased claudin-7 expression (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others, epithelial-specific Ets-1 and Sp1 play an active role in EpCAM promoter regulation 37 , while transcription factor nuclear factor-kappa B(NF-KB)and p53 have been described as transcriptional repressor of EpCAM 47 . TACE-dependent EGFR axis 57 , Claudin-7 and claudin-1 trafficked into lysosomes 58 and presenillins mediate PI3K/akt and ERK activation via select signaling receptors 59 ,which present a highlight mechanism in cancer. The emerging function of EpCAM in cell proliferation, migration and possibly cancer initiation broadens the interest to use EpCAM as an immune target, antibodybased clinical trials and in 2009, the European Medicines Agency approved the use of tri functional bi specific antibody Catumaxomab, which binds to EpCAM oncogenic receptor and enhances the immunological response against EpCAM-positive cells in malignant ascites 43 .…”
Section: Signal Transduction By Epcam Oncogenic Receptor and Its Targmentioning
confidence: 99%
“…TACE-dependent EGFR axis [109,110], Claudin-7 and claudin-1 trafficked into lysosomes [111] and presenillins mediate PI3K/akt and ERK activation via select signaling receptors [112], which present a highlight mechanism in cancer.…”
Section: Epcam Nuclear Signalingmentioning
confidence: 99%